Lodz in the process of deindustrialization. Social aspects of 1990–2004 systemic transformation - Wielisława Warzywoda-Kruszyńska; Kamil Kruszyński (Acta Universitatis Lodziensis: Folia Sociologica, 2023)
The aim of this article is to present a brief history of Lodz in view of historical events leading to the deindustrialization of the city during the period of Poland’s economic transformation. As a “great change” trauma of 1990 to 2004, juvenilization of poverty in Lodz has been documented. This phenomenon seems to be disregarded and unnoticed by architects and implementers of the transition from a centrally planned economy to a market economy.